THE KARYOTYPE OF SEVEN SPECIES OF AMPHIBIANS (ANURAN ORDER) FROM SOUTH-EAST SULAWESI - -, Nasaruddin; -, Suriana; Arinto Adi, Dwi; -, Salamansyah (Jurnal Veteriner; Vol 10 No 2 (2009), 2009)
As chromosome of different species differs in the size, shape, and number, their caryotpes areexpected to provide a distinctive and characteristic feature of the organism. The caryotypes ofseven amphibian species : Limnonectes gruniens, L modestus, Rana (Hylarana) chalconota,Fajervarya cancrivora, Polypedates celebensis, Bufo celebensis and B biporcatus of South EastSulawesi-origin were investigated. The result showed that the number of diploid chromosomes inthe seven anuran varied between 22-26. The highest diploid chromosomes were observed in Rchalconota, F cancrivora (26), followed by L gruniens, L modestus (24) and the lowest were observed22 in P celebensis, B celebensis and B biporcatus (22). In general, all the the seven anuran sharesfour metacentric chromosomes pairs which is in pairs No 5, 6, 9, and 10 respectively. Howeverdifferences were observed in other chromosomes pairs numbers among the seven species.
Keywords: chromosomal, caryotypes, amphibian